2018
DOI: 10.1002/aqc.2936
|View full text |Cite
|
Sign up to set email alerts
|

Residency and reproductive status of yellowfin tuna in a proposed large‐scale pelagic marine protected area

Abstract: Since the year 2000, the designation of remote, large‐scale marine protected areas (LSMPAs) has closed over 15 × 106 km2 of ocean to commercial fishing. Yet, while these mega‐reserves have collectively made a major contribution toward meeting global targets for marine conservation, their effectiveness for the protection of highly mobile, pelagic species remains largely unknown. This study reports on the spatial behavior and reproductive status of yellowfin tuna (Thunnus albacares) inhabiting a proposed LSMPA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 46 publications
3
19
0
Order By: Relevance
“…The contrasting movement patterns exhibited by different yellowfin life stages and studies conducted over a decade apart have demonstrated that tuna movement between tropical and temperate regions remains inadequately understood (Holland et al, 1999;Pecoraro et al, 2017Pecoraro et al, , 2018Anderson et al, 2019). As the Central North Pacific faces various anthropogenic stressors (Erauskin-Extramiana et al, 2019;Woodworth-Jefcoats et al, 2019) and stakeholders experience potential changes to fisheries management and conservation measures such as creation of large-scale marine protected areas (Richardson et al, 2018;Hernández et al, 2019), availability of yellowfin tuna and economic impacts to local communities will remain a serious issue.…”
Section: Discussionmentioning
confidence: 99%
“…The contrasting movement patterns exhibited by different yellowfin life stages and studies conducted over a decade apart have demonstrated that tuna movement between tropical and temperate regions remains inadequately understood (Holland et al, 1999;Pecoraro et al, 2017Pecoraro et al, , 2018Anderson et al, 2019). As the Central North Pacific faces various anthropogenic stressors (Erauskin-Extramiana et al, 2019;Woodworth-Jefcoats et al, 2019) and stakeholders experience potential changes to fisheries management and conservation measures such as creation of large-scale marine protected areas (Richardson et al, 2018;Hernández et al, 2019), availability of yellowfin tuna and economic impacts to local communities will remain a serious issue.…”
Section: Discussionmentioning
confidence: 99%
“…It has therefore been suggested that the BIOT MPA would have little conservation value for tropical tunas as they are too mobile (Dueri and Maury, 2013) and would simply displace fishing effort (Kaplan et al, 2014). Yet, the importance of oceanic islands for tropical tunas is being revealed in the Atlantic (Richardson et al, 2018) and the Pacific (Boerder et al, 2017). Indeed, tagging studies from within BIOT have only reported limited evidence of emigration by pelagic predators such as blue marlin (Makaira nigricans), sailfish (Istiophorus platyperus), silky sharks (Carcharhinus falciformis), and yellowfin tuna, although it should be noted that tag numbers were relatively low and tag duration limited (Carlisle et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In a counter example, it was deemed unlikely that a proposed MPA at Ascension Island (tropical Atlantic) would lead to population benefits for the yellowfin tuna population; although individuals spent several months at a time foraging around the island, they were not found to be reproductively active (Richardson et al, 2018). In an example from a highly migratory species with a very different life cycle, tagging studies on green turtles in the Chagos Archipelago MPA indicate that turtles spend a very small proportion of time inside the MPA, using it for nesting but not for foraging (Hays et al, 2014;Naro-Maciel et a!., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, tagging data suggest stock structure and regional retention on large spatial scales for bigeye tuna (Schaefer et al, 2015) and that yellowfin tuna will remain in an area similar in size to PIPA for periods of weeks to months (Richardson et al, 2018;Schaefer et al, 2011). A global synthesis of dart tag data indicated that all three tropical tuna species are capable of both rapid large-scale movements and regional fidelity or periodic returns to feeding and spawning locations (Fonteneau and Hallier, 2015).…”
Section: Discussionmentioning
confidence: 99%